Conducting Polyanethole /Metals Oxides Nanocomposites for Corrosion Protection and Bioactivity - Ayat Monther Alqudsi; Khulood Abid Saleh (مجلة بغداد للعلوم)
Corrosion is critical to a researcher since it has a substantial impact on both people's safety and the economy. A new approach based on a unique material has been employed to prevent rusting. Conducting polymer-composites are material types that show promise for anticorrosion by electrochemical synthesis of polyanethole(PA)/metals oxide nanocomposite (ZnO,TiO2) on Stainless Steel 304L (SS-304L) which plays as working electrode by using electropolymerization technique. The synthesized coating polymer was characterized by Fourier transform-infrared spectroscopy (FTIR) and atomic force microscopy (AFM) checkups. The findings demonstrated that when compared to the blank SS- 304L, PA/Nano composite and PA provide the strongest corrosion defenses for the metal. The results explained that the corrosion protection increased from 71% for PA film to 98% for PA/ZnO film  and to 87% for PA/TiO2  at 298K .In addition, calculations were made for the kinetic and thermodynamic parameters (Ea, A, ∆H, ∆S and ∆G). Escherichia coli and Staphylococcus aureus, two gram-positive and gram-negative bacteria, were used to test the biological activity of polymeric film (E.Coli).